2021
DOI: 10.1530/ec-21-0199
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between adenosine deaminase and heart rate-corrected QT interval in type 2 diabetic patients

Abstract: Background: Prolonged heart rate-corrected QT (QTc) interval may reflect poor prognosis of patients with type 2 diabetes (T2D). Serum adenosine deaminase (ADA) levels are related to hyperglycemia, insulin resistance (IR) and inflammation, which may participate in diabetic complications. We investigated the association of serum ADA levels with prolonged QTc interval in a large-scale sample of patients with T2D. Methods: In this cross-sectional study, a total of 492 patients with T2D were recruited. Serum ADA l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…In addition, patients with increased cardiometabolic risks are always characterized by elevated serum ADA levels, and these cardiometabolic risks include higher BMI (35), increased TC (36), hypertension (16), atherosclerosis (13), thrombosis (14), coronary artery calcification (37) and T2D (38). Furthermore, in our previous studies and other previous studies, elevated serum ADA levels are not only involved in impaired pancreatic b-cell function in T2D (39) but also contribute to several diabetic complications, such as diabetic retinopathy (40), diabetic nephropathy (41), and prolonged heart QT interval in T2D (42). In our present study, serum ADA levels were observed to be positively correlated with ageing, higher SBP, longer diabetes duration, and increased levels of ALT, AST, GGT, CysC and HbA1c and negatively correlated with eGFR and insulin sensitivity index (IS-CP).…”
Section: Discussionmentioning
confidence: 71%
“…In addition, patients with increased cardiometabolic risks are always characterized by elevated serum ADA levels, and these cardiometabolic risks include higher BMI (35), increased TC (36), hypertension (16), atherosclerosis (13), thrombosis (14), coronary artery calcification (37) and T2D (38). Furthermore, in our previous studies and other previous studies, elevated serum ADA levels are not only involved in impaired pancreatic b-cell function in T2D (39) but also contribute to several diabetic complications, such as diabetic retinopathy (40), diabetic nephropathy (41), and prolonged heart QT interval in T2D (42). In our present study, serum ADA levels were observed to be positively correlated with ageing, higher SBP, longer diabetes duration, and increased levels of ALT, AST, GGT, CysC and HbA1c and negatively correlated with eGFR and insulin sensitivity index (IS-CP).…”
Section: Discussionmentioning
confidence: 71%
“…The CHD was independently associated with QTc interval prolongation even after adjustment for age and sex [ 7 ]. A recent study found that female gender and treatment with insulin sensitizers were the independent contributors for QTc interval prolongation [ 8 ]. QTc was found to independently predict all-cause mortality in a prospective cohort of people with type 2 diabetes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%